Redescription of the South African millipede Cylichnogaster lawrencei Verhoeff, 1937 and notes on the family Siphonotidae (Diplopoda, Polyzoniida) - Shear, William A. (Zootaxa, 2016)
The unusual millipede Cylichnogaster lawrencei Verhoeff, 1937 (Diplopoda, Polyzoniida, Siphonotidae) is redescribed from newly collected specimens. Species of Cylichnogaster are the only known colobognathan millipedes capable of volvation, and are also distinguished by their small size and low segment number. Taxonomic notes are provided on the poorly known family Siphonotidae.